Brain Fingerprinting – A Scientific Technique for Solving Crimes: Advancing Investigations through Brain Wave Analysis (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In the field of criminology various technological innovations have signaled milestone changes in how the system conducts investigations. One such new technology carries with it an emerging potential to revolutionize the investigatory landscape Brain Fingerprinting. This technique is believed to be the finest lie detector on hand and is said to identify even those criminals who pass the polygraph test i.e the conventional lie detector test with ease. The new method employs brain waves, which are useful in detecting whether the person subjected to the test, remembers finer details of the crime. Even if the person willingly silent or keeps secret the essential information, the brain wave is sure to trap him.BF has proven 100% accurate more than 120 tests, including tests on Special Force agents, tests for an Intelligence agency and also for the real-life situations including lawbreaking crimes. This technique is based on finding that the persons asked to lie show different patterns of brain activity than they do when being truthful.